Український кубофутуризм: екстерівський варіант - Столярчук, Наталія; Stolyarchuk, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано філософсько-естетичні, художньо-стильові та національні особливості україн-ського авангардного мистецтва, а в його контексті визначено самобутність вітчизняного кубофутуризму як унікального напряму європейського авангарду. Основу дослідження становить творчість О. Екстер – заснов-ниці українського кубофутуризму. The article analyzes the philosophical-aesthetic, art style, and the national peculiarities of the Ukrainian avant-garde art and its context is determined by the identity of the domestic kubofuturizma as a distinct European avant-garde. In particular it is proved that the ideological, philosophical and aesthetic basis of Russian avant-garde was formed as a gradual process of synthesis of Western philosophical traditions with those of their own national culture (folklore, Ukrainian iconography, artistic and aesthetic ideas of the Baroque). On this basis, the Ukrainian avant-garde artists introduced new artistic direc-tions,among which the most powerfully declared itself the kubofuturizma. When this research is the work of A. Exter − founder of the Ukrainian kubofuturizma.
Ukrainian Kubofuturizma: Exter’s Variant
Keywords: авангардизм; avant-garde; кубофутуризм; kubofuturizma; новаторство; innovation; традиції; tradition; колорит; flavor; конструктивізм; constructivism; сценографія; scenography